Thermoelectric and magnetic properties of La 0.7 (Sr 1-x Ca x) 0.3 MnO 3 synthesized by tThermal hydro-decomposition method - Pinitsoontorn, Supree; Phewbang, Muttika (Asia-Pacific Journal of Science and Technology, 2017)
La 0.7 (Sr 1-x Ca x ) 0.3 MnO 3 powders for x = 0.0, 0.2, 0.4, 0.6, 0.8 and 1.0 were synthesized by a thermal hydro-decomposition method using metal acetate salts and de-ionized water as starting materials. The physical properties of the samples were characterized by thermogravimetric/ differential thermal analysis (TG/DTA), x-ray diffraction (XRD), energy dispersive x-ray analysis (EDX) and scanning electron microscopy (SEM). The single phase of La 0.7 (Sr 1-x Ca x ) 0.3 MnO 3 compound was obtained at the calcined temperature of 800 o C for 4 h, but some second phases were still observed. The polycrystalline bulk samples were compacted by a uniaxial pressure of 50 MPa and then sintered at 1,200 o C for 6 h.The second phases were disappeared. The thermoelectric properties of the sintered samples were investigated at room temperature and found that at x = 1.0, the electrical resistivity and the Seebeck coefficient were 2.2 ?cm and 91 ?VK -1 , respectively. The magnetic properties study showed that at x = 0 the maximum magnetization was found to be 20 emu/g.